Effect of mitochondrial coenzyme‐Q10 precursor solanesol in gentamicin‐induced experimental nephrotoxicity: Evidence from restoration of ETC‐complexes and histopathological alterations - Minakshi Sangwan; Hema Chaudhary; Sidharth Mehan; Zuber Khan; Ammar A. Bahauddin; Bandar D. Alrehaili; Hossein M. Elbadawy; Mohannad A. Almikhlafi; Acharan S. Narula; Reni Kalfin; Hanna Wanas (Wiley, 2024)
Abstract Nephrotoxicity occurs when the body is exposed to certain drugs or toxins. When kidney damage occurs, the kidney fails to eliminate excess urine and waste. Solanesol (C45H74O) is a tri‐sesquiterpenoid alcohol first isolated from tobacco, and it is widely distributed in plants of the Solanaceae family. Solanesol (SNL) is an intermediate in the synthesis of coenzyme Q10 (CoQ10), an antioxidant which protects nerve cells. This study investigated the protective effect of SNL at doses of 30 and 60 mg/kg in gentamicin‐induced nephrotoxicity in Wistar albino rats. Animals were distributed into six groups and administered 100 mg/kg gentamicin‐intraperitoneal injection for 14 days. Biochemical assessments were performed on kidney homogenate, blood, and serum. Treatment with SNL was shown as lower serum levels of creatinine, blood urea nitrogen (BUN), thiobarbituric acid reactive substances (TBARS), and Tumor necrosis factor alpha)TNF‐α ((p < .001). It also restored reduced glutathione (GSH) and mitochondrial complex enzymatic activity as protective measures against gentamicin‐induced nephrotoxicity. SNL were shown to reduce inflammation and oxidative stress markers (p < .001). Histological findings furtherly augmented the protective effects of SNL. Long‐term SNL therapy also restored mitochondrial electron transport chain complex enzymes, such as complex‐I (p < .001). In conclusion, these findings suggest that SNL can represent a protective therapeutic option for drug‐induced nephrotoxicity, a long‐term adverse effect of aminoglycoside antibiotics such as gentamicin.